Shear strengthening of reinforced concrete deep beams with highly ductile fiber-reinforced concrete jacket. (1st May 2022) - Li, Ruizhe; Deng, Mingke; Zhang, Yangxi; Wei, Ding
Abstract: This paper presents an experimental work on the shear behavior of reinforced concrete (RC) deep beams strengthened with highly ductile fiber-reinforced concrete (HDC) jackets. The test variables included the shear-span-to-effective-depth ratio, presence or absence of internal stirrups, the internal shear reinforcement ratio, the thickness of the U-shaped jacket (15 mm and 25 mm), the types of the matrix (HDC and mortar), and the presence or absence of stirrups in jackets. A total of seventeen beams were loaded under three-point bending test in two batches. The failure modes, load-deflection curves, and load-strain curves were described and analyzed. The test results revealed that the shear strengthening effectiveness of the HDC jacket for RC beams was obvious. The RC beams strengthened with HDC had a better cracking pattern and failure mode compared with the reference specimens and the beam strengthened by mortar. The shear capacity of the beams strengthened with HDC was improved by 13.6%–145.5%. The shear capacity of the HDC jacket-retrofitted specimen increased significantly by configuring stirrups in the jacket or increasing the jacket thickness. The shear strengthening effectiveness of HDC jacket revealed an upward trend with an increase in shear-span-to-effective-depth ratio. The strength of stirrups in HDC jacket was effectively utilized, mainly because HDC jacket showed a good synergistic performance with the internal RC beam. Furthermore, in order to calculate the shear capacity of the beams strengthened with HDC, the direct strut-and-tie model (DSTM) was adopted and modified. The results of the calculation correlated well with existing experimental results. Highlights: HDC has an obvious advantage for shear strengthening of shear-deficient beams. The shear load capacity of strengthened RC beams was significantly increased. The strengthening stirrups in HDC jackets can be effectively utilized. The direct strut-and-tie model was used to predict the shear capacity.